Analisis Manfaat Contextual Teaching and Learning dalam Pendidikan Akidah - Gibran, Achmad Fawwas; Lisnawati, Santi; Alim, Akhmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the benefits of the Contextual Learning Approach (CTL) in Aqeedah education. The methodology employed is a Systematic Literature Review (SLR), following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Researchers successfully collected 158 articles from the Google Scholar database within the past ten years (2015-2024) after following the four steps of the PRISMA procedure: Identification, Screening, Eligibility, and Inclusion. Ultimately, 12 articles were selected as research material. The analysis reveals that the Contextual Learning Approach significantly benefits Aqeedah education. From the examination of these twelve articles, six key advantages of CTL in Aqeedah education have been identified: First, it improves learning outcomes. Second, it enhances motivation and interest in learning. Third, it increases student participation. Fourth, it fosters a conducive learning environment. Fifth, it promotes student independence. Lastly, it serves as a means of character development. The Contextual Learning Approach can effectively create a mindful, meaningful, and joyful atmosphere for learning in Aqeedah education. It is crucial to garner support from various stakeholders to ensure that the benefits of this educational approach extend beyond academic achievement, thereby strengthening Aqeedah and instilling noble values.